From connectivity to autonomy: the dawn of self-evolving communication systems - Nezami, Zeinab; Shah , Syed Danial Ali; Hafeez , Maryam; Djemame , Karim; Zaidi, Syed Ali Raza (Frontiers in Communications and Networks, 2025)
This paper envisions 6G as a self-evolving telecom ecosystem, where AI-native capabilities enables dynamic adaptation, autonomy, and resilience beyond traditional connectivity. We present a conceptual framework integrating reconfigurable infrastructure, adaptive middleware, and intelligent network functions, augmented by multi-agent collaboration to support distributed decision-making and scalable automation. The paper outlines how these components can align with emerging industrial frameworks, ensuring seamless integration within smart manufacturing processes. Rather than offering empirical results, we articulate a forward-looking architecture and discuss its implications for real-time responsiveness, efficiency, and robustness in future networked control systems. Ethical, standardization, and deployment considerations are examined, culminating in a proposed technology stack to guide ongoing research and implementation. By synthesizing current trends in AI and telecom convergence, this work aims to inform the development of intent-aware, resilient, and adaptive communication systems for 6G and beyond.